2015
DOI: 10.1177/1082013214566478
|View full text |Cite
|
Sign up to set email alerts
|

Steady, dynamic, creep/recovery, and textural properties of yoghurt/molasses blends: Temperature sweep tests and applicability of Cox–Merz rule

Abstract: In this study, physicochemical, rheological (steady, dynamic, and creep/recovery), and textural properties of yoghurt/molasses blends (0, 5, 10, and 15% molasses) were investigated. The blends showed shear thinning behavior, as described by Ostwald de Waele model (R(2) ( )≥ 0.955). Consistency coefficient value (K) of the blends decreased with increasing molasses concentration in the sample. Storage modulus (G') of blends was higher than loss modulus (G″), exhibiting weak gel-like behavior. Molasses addition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Table 5 showed that the G′, G″, and η * values at 6.28 rad/s for yogurt substituted with UDP were significantly lower than the control (p < 0.05), and significantly decreased with increasing the concentration of UDP from 0.2% to 0.6% (w/v). Similar trends on G′, G″, and η * values were observed in yogurt added with different concentration of mulberry molasses (Eroglu et al, 2016).…”
Section: Frequency Sweep Measurementsupporting
confidence: 77%
See 1 more Smart Citation
“…Table 5 showed that the G′, G″, and η * values at 6.28 rad/s for yogurt substituted with UDP were significantly lower than the control (p < 0.05), and significantly decreased with increasing the concentration of UDP from 0.2% to 0.6% (w/v). Similar trends on G′, G″, and η * values were observed in yogurt added with different concentration of mulberry molasses (Eroglu et al, 2016).…”
Section: Frequency Sweep Measurementsupporting
confidence: 77%
“…The magnitudes of slopes, intercepts, and R 2 are shown in Table . Generally, true gels have zero slopes in the plots of log G ′ and log G ″ versus log ω while weak gels have positive slopes and the value of K ′ is higher than K ″ over the frequency range (Erogluet al, ). The results indicated that all samples exhibited weak gel behaviors as the values of n′ and n″ were positive and the K ′ value was higher than the K ″ value for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the stable trend in values could also be explained by denaturation of the protein found in casein gels, according to Eroglu et al, who studied the temperature sweep tests for analysis of the rheological behavior of yogurt and yogurt/ molasses blends. 25 Finally, G′ and G″ values showed a drastically increasing trend with temperature higher than 80 °C, especially higher than 90 °C. This could be due to the loss of most moisture from gels and aggregation produced by hydrophobic interaction or covalent cross-linking, which would lead to the formation of the gelatine network.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Loss of moisture, breakage of some weak chemical bonds, and a little heat-cross-linking of the small-molecular-weight casein were all in this state for reaching equilibrium. Additionally, the stable trend in values could also be explained by denaturation of the protein found in casein gels, according to Eroglu et al, who studied the temperature sweep tests for analysis of the rheological behavior of yogurt and yogurt/molasses blends . Finally, G ′ and G ″ values showed a drastically increasing trend with temperature higher than 80 °C, especially higher than 90 °C.…”
Section: Resultsmentioning
confidence: 98%
“…G ′ values of the samples inoculated by strains S2, S4 and S6 were clearly higher than those of the samples inoculated by strains SR and SC1, suggesting the former were more elastic in their behaviour than the latter. The positive and parallel slopes of all the curves and the thixotropic time-dependent property indicate that the gels of the samples fermented by the indigenous strains of Lait caillé could be considered structurally as weak gels (Eroglu et al ., 2014; Douglas, 2018). Weak gels will display homogeneous flow conditions when submitted to high shear stresses, while strong gels will display breaking on a non-homogenous surface (Douglas, 2018).…”
Section: Discussionmentioning
confidence: 99%